Etika Digital dalam Praktik Hukum Adaptasi Profesi Hukum di Era Teknologi - Rendhi Renaldhi; Nita Yunita; Arif Hardiyanto; Toto Hartono; Sena Narenda; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article examines the dynamics of legal professional ethics in the context of advancements in information technology. In the modern legal system, the use of technologies such as e-courts, cloud-based storage, and AI integration introduces new consequences for the practices and ethical standards of the legal profession. This paper highlights these challenges and proposes a reorientation of the legal ethics approach based on technological adaptation. The research is normative, employing a conceptual approach to the values of legal professional ethics, particularly in the practices of advocates and paralegals, and analyzes relevant literature and legal frameworks.